AB0843 Case-Finding for Joint Pain and Anxiety and Depression: the Enhance Study. (9th June 2015) - Jinks, C.; Morden, A.; Chew-Graham, C.; Porcheret, M.; Finney, A.; Dziedzic, K.; Healey, E.L.; Tan, V.; Cooper, V.; Jordan, J.; Mallen, C.
Abstract : Background: Osteoarthritis (OA) related joint pain and mental health problems are common and often co-exist in patients with other long term conditions (LTCs), but are under-detected and sub-optimally managed in primary care. The ENHANCE study aims to develop and test the feasibility and acceptability of a practice nurse-led "enhanced" review for identifying, assessing and supporting management of joint pain, anxiety and/or depression in patients attending routine LTC reviews. We report on the development of the new complex intervention. Objectives: To use a theoretically informed approach to co-design an intervention for case-finding and initial management of OA related joint pain and anxiety and/or depression in routine consultations for LTCs in primary care. Methods: An implementation of change model was used in three parts. (1) A "concrete proposal" for the intervention was co-produced using an evidence synthesis and a community of practice (CoP) (patient and practice nurse advisory groups and 3 stakeholder workshops). (2) A target group analysis was undertaken using a focus group with practice nurses (n=6) to identify current practice and potential determinants of behaviour change required to deliver the new intervention. Data were analysed thematically and then mapped to the Theoretical Domains Framework. (3) Training needs and techniques to address determinants of nurse behaviour highlighted in part 2 were identified and integrated into the trial training programme. Results: (1) Through collaborative working an algorithm for the enhanced review consultation was produced. This includes tools for case-finding and initial assessment, evidence based treatment options (e.g. based on NICE guidelines), and signposting options to other services including the third sector. (2) In the focus group, practice nurses understood the new complex intervention but highlighted potential treatment burden for patients. Issues related to capabilities and professional roles were evident as they talked of a lack of knowledge, confidence and skills to undertake OA case-finding, joint assessments and initial management. Practice nurses were more confident in asking about anxiety and depression but disclosed avoidance of this activity in practice. (3) In addition to knowledge, confidence and skills for dealing with OA, training needs in detecting non-verbal cues which might suggest anxiety and/or depression were highlighted, as were strategies for providing reassurance about their own decisions (and consequences) and emotional support or supervision during the intervention period. Conclusions: An implementation of change model has been applied using an evidence synthesis, community of practice and focus group with practice nurses. This approach has enabled co-design of a new complex intervention for integrating joint pain and anxiety and/or depression into LTC reviews in primary care consultations, and identification of training needs. A feasibility stepped wedge trial will now commence. Acknowledgements: Independent research funded by the National Institute Health Research (NIHR) Collaborations for Leadership in Applied Health Research and Care West Midlands. CM is supported through a NIHR Research Professorship (NIHR-RP-2014-04-026). Views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: None declared